Tindak Pidana Penipuan Dengan Modus Menjanjikan Kelulusan Anggota TNI (Studi Kasus Putusan No. 37-K/PM.I-05/AD/VIII/2024) - Amanda, Nadia Pradita; Anshari, Ashari; Kurniawan, Heru Yudi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
This study is motivated by the increasing number of fraud crimes involving the modus operandi of promising guaranteed acceptance into the Indonesian National Armed Forces (TNI) recruitment process, as exemplified in Court Decision No. 37-K/PM.I-05/AD/VIII/2024. The purpose of this research is to conduct a juridical analysis of such fraud and to examine the judge’s legal considerations in adjudicating the case. The research employs a descriptive-analytical method aimed at systematically presenting the legal facts in the decision and analyzing them based on applicable legal norms. A normative legal research type is used, focusing on the provisions of Article 378 of the Indonesian Criminal Code (KUHP) in conjunction with Article 55 paragraph (1) KUHP, while also reviewing the application of these criminal elements in the military court’s ruling. Data were analyzed qualitatively by describing the application of criminal elements, assessing the judge’s legal reasoning, and connecting them with principles of justice and relevant legal theories. The findings indicate that fraud by promising acceptance into the TNI fulfills the elements of Article 378 KUHP. The panel of judges considered key aspects such as malicious intent, the financial loss suffered by the victim, and the broader social impact of the defendants’ actions, although the ruling is still subject to discussion regarding its reflection of substantive justice. Keywords: Fraud Crime, Judge Consideration, Military Court.